Neutralizing Anti-gH Antibody of Varicella-Zoster Virus Modulates Distribution of gH and Induces Gene Regulation, Mimicking Latency - Shiraki, Kimiyasu (American Society for Microbiology, 2011)

(untitled)
The anti-glycoprotein H (gH) monoclonal antibody (anti-gH-MAb) that neutralizes varicella-zoster virus (VZV) inhibited cell-to-cell infection, resulting in a single infected cell without apoptosis or necrosis, and the number of infectious cells in cultures treated with anti-gH-MAb declined to undetectable levels in 7 to 10 days. Anti-gH-MAb modulated the wide cytoplasmic distribution of gH colocalized with glycoprotein E (gE) to the cytoplasmic compartment with endoplasmic reticulum (ER) and Golgi markers near the nucleus, while gE retained its cytoplasmic distribution. Thus, the disintegrated distribution of gH and gE caused the loss of cellular infectivity. After 4 weeks of treatment with anti-gH-MAb, no infectious virus was recovered, even after cultivation without anti-gH-MAb for another 8 weeks or various other treatments. Cells were infected with Oka varicella vaccine expressing hepatitis B surface antigen (ROka) and treated with anti-gH-MAb for 4 weeks, and ROka was recovered from the quiescently infected cells by superinfection with the parent Oka vaccine. Among the genes 21, 29, 62, 63, and 66, transcripts of gene 63 were the most frequently detected, and products from the genes 63 and 62, but not gE, were detected mainly in the cytoplasm of quiescently infected cells, in contrast to their nuclear localization in lytically infected cells. The patterns of transcripts and products from the quiescently infected cells were similar to those of latent VZV in human ganglia. Thus, anti-gH-MAb treatment resulted in the antigenic modulation and dormancy of infectivity of VZV. Antigenic modulation by anti-gH-MAb illuminates a new aspect in pathogenesis in VZV infection and the gene regulation of VZV during latency in human ganglia.